Pengembangan Bakat Dan Minat Peserta Didik Di Smp Negeri 1 Tilatang Kamang Provinsi Sumatera Barat - Ari Nasowaloon Harahap; Afrinaldi Afrinaldi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research problem arises from the need to understand and analyse the Talent and Interest Development of Learners at SMP Negeri 1 Tilatang Kamang, West Sumatra. The purpose of the study was to explore the holistic approach applied by the school in developing learners' talents and interests, as well as to identify the impact of the development strategies implemented. The research methodology used a descriptive qualitative approach with data collection through interviews, observation, and document analysis. Teachers, students, and other related parties at SMP Negeri 1 Tilatang Kamang became the research subjects, who provided a comprehensive view related to the development of talents and interests. This research contributes an in-depth understanding of the implementation of talent and interest development at SMP Negeri 1 Tilatang Kamang, with positive implications for learners' personal and academic development. The results show that the school applies a holistic education philosophy by forging close partnerships with the local community, industry and local artists. Teachers play an active role as mentors, and the inclusive grading system creates an environment that stimulates learners' development in various areas. Diverse extracurricular activities and the integration of practical skills in learning result in learners who are not only academically competent but also prepared to face future challenges